A historiographical approach to the lesbian movement in the West. A parallel vision - Vásquez-Parra, José Carlos (2023)
It is a challenge to approach a specific topic taking into account all its elements, especially when doing a historical analysis that needs to integrate all points of view about a situation, event or long period of time. Unfortunately, most of the approaches to the homosexual movement in the West are based on the perspective of gay men, leaving out of the narrative other parts of the collective, such as the lesbian group or the trans community.  For this reason, the aim of this article is to provide a historiographical approach to the lesbian movement, considering its international and Latin American perspectives. The intention is to be able to show how the social struggle of the LGBTIQA collective raises particularities that must be specified among its groups. This evidences the fact that it is impossible to have a single historical version and the need for parallel approaches that consider their similarities and differences.